"Nivel de autoestima y prácticas de autocuidado del Adulto Mayor con enfermedad renal en Hemodiálisis de una Clínica de Trujillo" - Becerra Julca, Anita Elizabeth (2016)
This research study descriptive - correlational aims to determine the relationship between self-esteem and self-care practices of the elderly with kidney disease on hemodialysis clinic Trujillo in 2015. This report is based on concepts Self-esteem theory of Maslow (2000) and self Dorothea Orem (1998). The sample consisted of 40 seniors who attended the hemodialysis service in the months of October to December 2014. Statistical analysis of the results was performed by applying the tests of independence criteria using the chi square test (X2) reached the following conclusions: 67.5 percent seniors in hemodialysis have a high level of self-esteem and low self-esteem have 32.5 percent, 55.0 percent seniors in hemodialysis have regular self-care practices and 35 percent have good self-care practices only 10 percent have poor self-care practices, 59.3 percent seniors in hemodialysis have self-regulating practices with a higher level of self-esteem; 46.2 percent Regular self-care practices with a low level of self-esteem; 40.7 percent good self-care practices with a high level of 30.8 percent self-esteem and poor self-care practices with a low level of self-esteem and only 23.1 percent of good practices with a level of self-esteem alt, there is a statistically significant relationship between the levels of esteem and self-care practices